2008
DOI: 10.1089/aid.2007.0304
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Characterization and Comparison of Full-Length Envelope Glycoproteins from South African HIV Type 1 Subtype C Primary Isolates That Utilize CCR5 and/or CXCR4

Abstract: CCR5 has preferentially been used by all circulating HIV-1 subtype C viruses for cell entry. Recently, we reported the highest proportion of CXCR4-utilizing primary isolates among a cohort of 20 South African AIDS patients. This study describes and compares the Env genotypic characteristics from these 20 HIV-1 subtype C (and unique CD recombinant) primary isolates. Fourteen primary isolates utilized CCR5, four (including the CD recombinant) used CXCR4, and two were dual tropic. Extensive analysis and compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Recombinants were further evaluated with the Recombinant Identification program (RIP 3.0) and jumping profile Hidden Markov Model 25 (jpHMM-HIV; http://www.hiv.lanl.gov). In addition, matched env was PCR amplified, sequenced, and extensively analyzed 26 for further clarification of selected samples. When sequence data were available, epidemiological linkage for suspected 6 PRICE ET AL.…”
Section: Genotypingmentioning
confidence: 99%
“…Recombinants were further evaluated with the Recombinant Identification program (RIP 3.0) and jumping profile Hidden Markov Model 25 (jpHMM-HIV; http://www.hiv.lanl.gov). In addition, matched env was PCR amplified, sequenced, and extensively analyzed 26 for further clarification of selected samples. When sequence data were available, epidemiological linkage for suspected 6 PRICE ET AL.…”
Section: Genotypingmentioning
confidence: 99%
“…[16][17][18][19][20] However, recent studies have found CXCR4-using viruses in about 30% of subtype C-infected patients with advanced disease. [21][22][23][24][25] Whether this apparent increased frequency of CXCR4-using subtype C viruses is due to better detection, the selection of CXCR4-using variants due to antiretroviral therapy, or an evolving epidemic, remains to be determined. Little is known about the genotypic determinants of CXCR4 coreceptor usage by subtype C viruses, and this information is crucial before genotypic analyses can be used to predict the tropism of this subtype.…”
Section: Introductionmentioning
confidence: 99%
“…We compiled a dataset of 645 HIV-1 subtype C V3 loop sequences of known coreceptor phenotypes based on coreceptor-transfected cell lines for CCR5 or CXCR4 coreceptor usage or MT-2 cells for non-syncytium-inducing (NSI) and syncytium-inducing (SI) properties, from the Los Alamos database (http://www.hiv.lanl.gov/) and from previously published literature [6,7,8,9]. Sequences containing #, $ or * were eliminated from the dataset.…”
Section: Tablementioning
confidence: 99%